Unleashing your language wizards a brain-based approach to effective editing and writing - Crow, John T. (Boston Pearson, 2010)
"Unleashing Your Language Wizards breaks new ground by presenting a research-based, active-learning approach to teaching lasting sentence management skills that taps into students? natural learning abilities. To guide teachers in grades 3-12 to effective teach editing and writing, this book introduces the basic principles, specific examples, and sample activities--all of which teach the most important language concepts from a variety of different angles and approaches--to help students conquer their written language issues. It focuses on three areas of knowledge?referred to as Wizards?that all students must possess to communicate effectively: Grammar Wizards, Sentence Wizards, and Rhetorical Wizards."--Publisher's description.
Background -- Meet Your Grammar Wizard -- Traditional Grammar Pedagogy and Brain-Based Learning -- The Grammar Wizard Approach -- Grammar Wizard Tests -- Grammar Wizard Activities -- Grammar Wizard Toolbox -- Brain-Based Punctuation -- Bridges -- Sentence Fluency -- Rhetorical Choices : Mechanics and Word Choice -- Rhetorical Choices : Structure.
Keywords: English language -- Composition and exercises -- Study and teaching (Elementary); English language -- Composition and exercises -- Study and teaching (Secondary); Language arts (Elementary)